По прочтению скандинавских переводов Б. Акунина (On Scandinavian Translations of B. Akunin) - Komarova, Olga (Poljarnyj vestnik, 2003)
The name of B. Akunin appeared on the Russian literary market five years ago. The author Grigory Tkhartishvili, a well-known man of letters, translator and a connoisseur of Japanese language and culture, is now known all over the world, and translations of his novels are widely available, including in Norway and Sweden. His novels are out of the ordinary not only as detective stories but also as works of postmodernist literature with intertextual connotations and complex historical and literary associations. The article presents an attempt to analyze certain peculiarities of his working methods, which present specific difficulties for translation into Norwegian and Swedish, such as verbal versatility and intertextual associations which are so important in postmodernist works. The article also deals with different translational strategies chosen by the translators in their rendering of realia, different social and local dialects and, what is most important - the intentional mannerisms of B. Akunin's artistic style.